Guided, internet based, cognitive behavioural therapy for post-traumatic stress disorder: pragmatic, multicentre, randomised controlled non-inferiority trial (RAPID). (16th June 2022) - Bisson, Jonathan I; Ariti, Cono; Cullen, Katherine; Kitchiner, Neil; Lewis, Catrin; Roberts, Neil P; Simon, Natalie; Smallman, Kim; Addison, Katy; Bell, Vicky; Brookes-Howell, Lucy; Cosgrove, Sarah; et al.
Abstract: Objective: To determine if guided internet based cognitive behavioural therapy with a trauma focus (CBT-TF) is non-inferior to individual face-to-face CBT-TF for mild to moderate post-traumatic stress disorder (PTSD) to one traumatic event. Design: Pragmatic, multicentre, randomised controlled non-inferiority trial (RAPID). Setting: Primary and secondary mental health settings across the UK's NHS. Participants: 196 adults with a primary diagnosis of mild to moderate PTSD were randomised in a 1:1 ratio to one of two interventions, with 82% retention at 16 weeks and 71% retention at 52 weeks. 19 participants and 10 therapists were purposively sampled and interviewed for evaluation of the process. Interventions: Up to 12 face-to-face, manual based, individual CBT-TF sessions, each lasting 60-90 minutes; or guided internet based CBT-TF with an eight step online programme, with up to three hours of contact with a therapist and four brief telephone calls or email contacts between sessions. Main outcome measures: Primary outcome was the Clinician Administered PTSD Scale for DSM-5 (CAPS-5) at 16 weeks after randomisation (diagnosis of PTSD based on the criteria of the Diagnostic and Statistical Manual of Mental Disorders, fifth edition, DSM-5). Secondary outcomes included severity of PTSD symptoms at 52 weeks, and functioning, symptoms of depression and anxiety, use of alcohol, and perceived social support at 16 and 52 weeks after randomisation. Results: Non-inferiority was found at the primary endpoint of 16 weeks on the CAPS-5 (mean difference 1.01, one sided 95% confidence interval −∞ to 3.90, non-inferiority P=0.012). Improvements in CAPS-5 score of more than 60% in the two groups were maintained at 52 weeks, but the non-inferiority results were inconclusive in favour of face-to-face CBT-TF at this time point (3.20, −∞ to 6.00, P=0.15). Guided internet based CBT-TF was significantly (P<0.001) cheaper than face-to-face CBT-TF and seemed to be acceptable and well tolerated by participants. The main themes of the qualitative analysis were facilitators and barriers to engagement with guided internet based CBT-TF, treatment outcomes, and considerations for its future implementation. Conclusions: Guided internet based CBT-TF for mild to moderate PTSD to one traumatic event was non-inferior to individual face-to-face CBT-TF and should be considered a first line treatment for people with this condition. Trial registration: ISRCTN13697710 .